Social Capital and Depressive Episodes: Gender Differences in the ELSA-Brasil Cohort - Souto, Ester Paiva; Moreno, Arlinda B.; Chor, Dóra; Melo, Enirtes C. Prates; Barreto, Sandhi M.; Nunes, Maria Angélica; Griep, Rosane Harter (Frontiers in Public Health, 2021)
Objective: This study investigates gender differences in the association of social capital with the incidence and maintenance of depressive episodes. Methods: Baseline and second wave data (4 years of follow-up) from the Longitudinal Study of Adult Health (ELSA-Brasil), a multicenter cohort of civil servants with 15,105 workers aged 35-74 years, were used. Social capital was assessed using the Resource Generator scale. Depressive episodes were assessed using the Clinical Interview Schedule - Revised (CIS-R). The statistical was performed using multinomial regression with adjustments for possible confounding factors. Results: Among men, low social capital in the "social support" dimension was associated with the incidence of depressive episodes (RR = 1.66; 95% CI: 1.01-2.72). Among women, social support was associated with the maintenance of depressive episodes (RR = 2.66; 95% CI: 1.61 - 4.41). Social capital was not associated with the incidence or maintenance of depressive episodes in the "prestige and education" dimension in both genders. Conclusion: The results highlight the importance of the dimension "social support" in both genders without its association with mental health. The resource-based social capital approach proved to be adequate for investigating mental health and confirms the idea that social networks can be useful in the treatment and prevention of depressive episodes.